Strategi Pemasaran Hotel Grand Asrilia di Masa Pandemi Covid-19 - Yuliana Pinaringsih Kristiutami (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2021)
The hospitality industry is one of the most significant contributions to the Indonesian economy. Bandung City is one of the areas in West Java that has quite a lot of hospitality companies. One of the hospitality companies in Bandung is Hotel Grand Asrilia. However, lately, it has been found a new type of virus that originated in Wuhan, China which caused the COVID-19 pandemic and brought enormous impact on the Indonesian economy even to the rest of the world. The purpose of this research is to find out the right strategy for Hotel Grand Asrilia in marketing its products during the COVID-19 pandemic. The method used in this study is a qualitative descriptive method with the technique of observation data retrieval, interviews, library studies also interpret and outlines the existing data in conjunction with the current situation. The result of this study proved that the application of marketing through digital marketing has a positive impact on Hotel Grand Asrilia where the use of digital marketing in the think is necessary especially in the middle of the COVID-19 pandemic so that business activities can continue to run and generate economic value.